Inguinal Bladder Hernia and Infravesical Obstruction: A Case Report on a Rare But Important Relationship - Cihangir Ulubey; Hakan Tekinaslan (Düzce Tıp Fakültesi Dergisi)
Bladder herniation is an uncommon clinical condition, comprising only 1-4% of all inguinal hernias, and is most frequently observed in elderly male patients. While many cases are asymptomatic, the presence of concomitant infravesical obstruction, such as benign prostatic hyperplasia (BPH), has been demonstrated to exacerbate symptoms and complicate management strategies. This case report aimed to present the comprehensive management of extraperitoneal bladder herniation in a 70-year-old male patient with a history of bilateral inguinal mesh hernia repair and significant BPH. The patient was treated via a single-incision surgical approach combining mesh hernia repair and open transvesical prostatectomy. This case report contributes valuable insights to the limited literature on combined surgical approaches for bladder herniation and BPH, and also underscores the significance of meticulous preoperative evaluation and multidisciplinary surgical planning in the successful treatment of complex urological cases.